Analysis of Numerical Methods for Droplet Impingement Characteristics under Aircraft Icing Conditions - Xiaobin Shen; Wenzhao Zhao; Zicheng Qi; Guiping Lin; Liangquan Wang (Aerospace, 2022)
The investigation of super-cooled droplet impingement characteristics is the most important step for aircraft icing and anti-icing/de-icing analyses. The Lagrangian method and the Eulerian method are widely used to compute the droplet motion and collection efficiency, and the two methods are considered to obtain almost the same results for surface impingement characteristics under icing conditions. The models and implementation approaches of the two methods were established in this work, and the simulations of droplet motion were carried out for a NACA 0012 airfoil, a 2D section of an A320 head, a multi-element airfoil, and an icing wind tunnel. The collection efficiencies of the NACA 0012 airfoil obtained by the present Lagrangian and Eulerian methods show good agreement with the results in the literature, validating the established methods. The droplet impingement characteristics of the two methods are consistent for the aircraft surfaces without upstream trajectory deflections. However, when the droplet motion is deflected by the frontal body before hitting the rear surfaces, the results obtained by the two methods are different whether the droplet trajectories intersect or not, which subverts the traditional opinion that the Lagrangian and Eulerian methods would obtain the same result of the droplet impingement characteristics. The reason is studied in detail according to the droplet motion results in the icing wind tunnel. The findings of this work are helpful for the accuracy of aircraft icing and anti-icing/de-icing simulations, and useful for the development of airworthiness certification.